Human Thrombi Contain an Abundance of Active Thrombin - Mutch, N. J.; Robbie, L. A.; Booth, N. A. (Thrombosis and Haemostasis, 2001)
This study assessed the abundance and activity of thrombin in human thrombi, removed at autopsy or during surgery. Arterial and venous thrombus sections showed thrombin activity by in situ zymography, based on conversion of fibrinogen to fibrin. Hirudin or antibodies to thrombin abolished the activity. Thrombin activity in extracts of 40 thrombi was quantified by cleavage of fibrinogen or small peptide substrates; the results correlated well (r = 0.87, p<0.0001) with a median activity of about 4.5 IU/g of thrombus (wet weight). Activity correlated poorly with total prothrombin (median 27 μg/g) and was inversely related to antithrombin, but not to PAI-1. Zymography showed two major active bands, thrombin at 37 kDa, and a 50 kDa form that probably corresponds to meizothrombin desF1. The abundant local thrombin demonstrated here has implications for thrombus lysis and extension; incomplete lysis and exposure of active thrombin may lead to re-occlusion of vessels.
Keywords: Thrombin; active; thrombus; re-occlusion